Crecimiento, mortandad y estado fitosanitario de la especie Copaifera paupera "copaiba" de la plantación N° 33 del CIEFOR - Puerto Almendra, Loreto - Perú. 2021 - Shapiama Rios, Inha Ana Nelida (2022)
The study was carried out in Forest Parcel No. 33 of 1 ha in Ciefor - Puerto Almendras, evaluating 200 Copaifera paupera “copaiba” plants, planted every 5 meters and in 10 strips. The greatest increase in diameter was presented by band 8 and 9 with a value of 0,20 cm between the first and last evaluation. Likewise, in height the greatest increase was presented by band 2 with a value of 4,15 cm. The Chi-square test indicates that there is a significant difference between the averages of increase in diameter - height and the bands (p-value = 0,00 <? = 0,05). The survival of cedar plants varies between 65% to 100% survival, while mortality varies between 5% to 35%. The highest number of plants presented GOOD quality with 156 seedlings that represents 78,39% of the total, followed by REGULAR quality with 19 live individuals that indicates 9,55 % and, finally, the least amount of individuals were observed in BAD quality with 3 seedlings that represented 1,51 % of the total. At a general level in the experiment Good quality (band 2, 6, 7, 8, 9 y 10) was recorded for the Copaifera paupera seedlings at the end of the study. Similar studies are needed with other native forest species in Ciefor - Puerto Almendras.